The Impact of Company Size, Earnings Volatility, and Dividend Yield on Stock Volatility of Issuers Listed on The JII During The Period 2020-2024 - Zuhriyah, Safiera; Widuri, Trisnia (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the effect of company size, earnings volatility, and dividend yield on stock volatility of JII issuers during 2020–2024. An associative quantitative method with secondary data from annual reports and daily stock prices was used, with 11 companies as the sample. Results show that company size and earnings volatility do not significantly affect stock volatility, while dividend yield has a significant negative effect. Collectively, the three variables significantly influence stock volatility. Dividend yield is a key factor in stock stability, whereas company size and earnings volatility are less dominant individually, providing implications for investors, management, and regulators.